Spontaneous Coronary Artery Dissection: Current State of the Science: A Scientific Statement From the American Heart Association - Hayes, Sharonne N; Kim, Esther S H; Saw, Jacqueline; Adlam, David; Arslanian-Engoren, Cynthia; Economy, Katherine E; Ganesh, Santhi K; Gulati, Rajiv; Lindsay, Mark E; Mieres, Jennifer H; Naderi, Sahar; Shah, Svati; et al. (Circulation (New York, N.Y.), 2018)
Spontaneous coronary artery dissection (SCAD) has emerged as an important cause of acute coronary syndrome, myocardial infarction, and sudden death, particularly among young women and individuals with few conventional atherosclerotic risk factors. Patient-initiated research has spurred increased awareness of SCAD, and improved diagnostic capabilities and findings from large case series have led to changes in approaches to initial and long-term management and increasing evidence that SCAD not only is more common than previously believed but also must be evaluated and treated differently from atherosclerotic myocardial infarction. High rates of recurrent SCAD; its association with female sex, pregnancy, and physical and emotional stress triggers; and concurrent systemic arteriopathies, particularly fibromuscular dysplasia, highlight the differences in clinical characteristics of SCAD compared with atherosclerotic disease. Recent insights into the causes of, clinical course of, treatment options for, outcomes of, and associated conditions of SCAD and the many persistent knowledge gaps are presented.